PSYCHOLOGICAL AND PEDAGOGICAL FUNDAMENTALS OF MANAGEMENT THE PROCESS OF FORMING A HEALTHY WAY STUDENTS' LIVES (Pedagogy of Higher and Secondary Education, 2008)
Healthy life style formation of student youth to put into effect according current training method to self - dépendant physical training lessons.